Evaluation of the health status of the Silverside (Odontesthes bonariensis) at a RAMSAR Site in South America - Ballesteros, Maria Laura (2017)
The objective of this work was to evaluate the health status of an economic and ecologically important fish species from Mar Chiquita Lake, a RAMSAR site located in Cordoba, Argentina, relative to the levels of selected persistent organic pollutants (POPs) in lake water and fish tissues. Odontesthes bonariensis was used as a model species, and its health was estimated by means of histological indices in gills and liver. Sampling was performed according to rainy and dry seasons (i.e. dry, rainy and post-rainy). Gill and liver histopathology were evaluated by semi-quantitative indices and morphometric analysis. Although epithelial lifting in gills and lipid degeneration in liver were frequently registered, they are considered as reversible if environmental conditions improve. During rainy and post-rainy seasons fish presented significantly higher scores of liver and total indices. These higher index scores were correlated with increased levels of POPs in gill and liver tissue. Therefore, preventive measures are needed to mitigate the entry of these compounds into the lake.